Literary Studies Deconstructed - Butler, Catherine. author. aut Link
IX, 149 p.
Keywords: Literary Studies Deconstructed critiques the state of Literary Studies in the modern university and argues for its comprehensive reconstruction. It argues that Literary Studies as currently practised avoids engaging with much of literary experience and prioritises instead the needs of critics as a professional community: to teach and assess students, to demonstrate the creation of knowledge, and to meet the demands of governments, funders and other bodies. The result is that many areas centrally important to lay readers are largely omitted from critical discussion. Moreover, critical writing and its conventions are framed so as to mask and repress the subject’s contradictions. This lively and provocative book will be of interest to undergraduate and postgraduate students with an interest in the critical profession or literary theory, as well as to Literary Studies academics.